STABLE ISOTOPE CHEMISTRY OF FOSSIL BONE AS A NEW PALEOCLIMATE INDICATOR - Kohn M.J.; Law J.M. (My University, 2006)
During fossilization, bone is thought to recrystallize and alter chemically on timescales of kyr to a few tens of kyr, i.e., similar to the timescale for formation of soils. Therefore, C- and O-isotope compositions of bone apatite should correlate with trends in soil water composition and aridity, and serve as paleoclimate indicators. This hypothesis was tested by analyzing C- and O-isotope compositions of the CO3 component of fossil bone apatite from mid-Oligocene through late Pleistocene units in Oregon and western Idaho, including the John Day (19.4-30.0 Ma), Mascall (15.2-15.8 Ma), and Rattlesnake (7.2-7.8 Ma) Formations, whose paleosol sequences have been studied in detail, and the Juntura (10-11 Ma), Hagerman (3.2 Ma), and Fossil Lake (<23-650 ka) fossil localities. tooth enamel ?18o values provide a baseline of meteoric water compositions. stable isotope compositions bone co3 do change in response to broad climatic trends, but show poor correlation with corresponding paleosol at specific horizons. instead, compositional deviations between and correlate the next higher paleosol; this suggests that timescale for fossilization exceeds one cycle. based on stratigraphic evidence simple alteration models, timescales are estimated 20-50 kyr, indicating will prove most useful sequences spanning>100 kyr. C-isotopes show negative and strong positive deviations during wet and dry climates respectively, and short-term trends correspond well with changes in aridity within the Mascall and Rattlesnake Formations, as inferred from paleosols. A proposed correction to ?18 O values based on ?13C anomalies implies a small, ?1.5? increase in meteoric water ?18O during the late Oligocene global warming event, consistent with a minimum temperature increase of ?4 deg;C. A strong inferred decrease in ?18O of 4-5? after 7 Ma closely parallels compositional changes in tooth enamel, and reflects a doubling in the height of the Cascade Range. ? 2005 Elsevier Inc. All rights reserved.
Keywords: BONE; FOSSIL; PROXY CLIMATE RECORD; STABLE ISOTOPE; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Палеоген::Олигоцен; Cenozoic::Quaternary::Pleistocene; Cenozoic::Paleogene::Oligocene